The Discrepancy Between Perceived Importance and Actual Delivery of Business Education in Residency: A Survey of Program Directors. Issue 5 (November 2020) - Patrinely, J. Randall; Davis, Matthew J.; Abu-Ghname, Amjed; Reece, Edward M.; Perdikis, Galen
Abstract : Background: In the contemporary healthcare environment, there is a need for physicians to understand business fundamentals. Nonsurgical residencies have implemented formal business education, but surgical training programs have been slower to adapt. Further research is needed to evaluate the status of business education in plastic surgery residency. Methods: A 12-question survey was created. Ninety program director (PD) e-mails were obtained and the survey was distributed using SurveyMonkey. The survey evaluated program demographics and current resources, commitments, and attitudes toward business training. The survey also identified the most important topics to include in a business curriculum. Results: Thirty-six surveys were completed (response rate = 40%). Whereas most PDs agreed that business education in plastic surgery residency was important (78%) and that their programs should have more business training (73%), only 39% currently offered business training. Only 42% of PDs believed that their chief residents were competent to handle the business aspects of plastic surgery upon graduation. No programs offered a formal gap year to pursue a professional business degree. The most important topics identified for a business curriculum were economics and finance (83.3%), management (64%), and marketing (53%). Conclusions: There is disconnect between perceived importance and resources available for plastic surgery residents to receive business education. Increased attention is needed to resolve this discrepancy to ensure that future plastic surgeons are equipped to excel in their personal careers and stimulate the advancement of the field. Future research should aim to outline a business curriculum for plastic surgery trainees.